2014
DOI: 10.1371/journal.pone.0087027
|View full text |Cite
|
Sign up to set email alerts
|

Interruption and Non-Adherence to Long-Term Adjuvant Hormone Therapy Is Associated with Adverse Survival Outcome of Breast Cancer Women - An Asian Population-Based Study

Abstract: This study aimed to evaluate the survival rate of women with breast cancer (BC) comparing persistence versus interruption and adherence versus non-adherence to adjuvant hormonal therapy (HT) in Asian population. Newly-diagnosed BC women from 2003 to 2010 were retrospectively identified from the Taiwan National Health Insurance Research Database. HT prescriptions were extracted to define treatment interruption and medication possession ratio. Their impacts on mortality were estimated by Cox regression with time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 18 publications
4
65
1
1
Order By: Relevance
“…(4) Furthermore, there is growing data showing that better adherence to endocrine therapy leads to higher survival rates. (79) Interventions that help patients adhere to prescribed endocrine therapy are needed.…”
Section: Inroductionmentioning
confidence: 99%
“…(4) Furthermore, there is growing data showing that better adherence to endocrine therapy leads to higher survival rates. (79) Interventions that help patients adhere to prescribed endocrine therapy are needed.…”
Section: Inroductionmentioning
confidence: 99%
“…Discontinuation or treatment interruption of hormone therapy (HT) may lead to an increase in breast cancer (BC) mortality . However, concerns have been raised by several studies that reported a suboptimal adherence and persistence to HT in BC patients .…”
Section: Introductionmentioning
confidence: 99%
“…The included studies focussed on a wide range of disease areas including pulmonary diseases, osteoporosis, depression, cardiovascular diseases, Parkinson's disease, epilepsy, chronic kidney disease, cancer and diabetes mellitus . Two studies did not measure disease‐specific medication (non‐)adherence .…”
Section: Resultsmentioning
confidence: 99%